"Like a fish out of water": The Big Five and Context Related Variables as Predictors for Expatriate Adjustment - Vetter, Ines (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2006)
Content of this study ist the examination of the influence of personality and context related variables on socio-cultural as well as psychological adjustment. A sample of 139 German speaking expatriates in China participated in standardized interviews and filled out a personality questionnaire (NEO-PI-R). Other-ratings of adjustment were provided by supervisors, colleagues, or employees (N=69) of the interviewee. Results show that with exception of Conscientiousness the Big Five predict adjustment. Likewise, context related variables were found to be related to the adjustment of expatriates.

Inhalt dieser empirischen Studie ist die Untersuchung des Einflusses von Persönlichkeit und kontextspezifischen Variablen auf die soziokulturelle und psychologische Anpassung. Eine Stichprobe von 139 deutschsprachigen Auslandsmitarbeitern in China nahm an standardisierten Interviews sowie an einem Persönlichkeitstest (NEO-PI-R) teil. Die Fremdeinschätzung der Anpassung erfolgte durch Vorgesetzte, Kollegen oder Mitarbeiter (N=69) der Interviewten. Die Ergebnisse zeigen, dass mit Ausnahme von Gewissenhaftigkeit, die Big Five Anpassung vorhersagen können. Ebenfalls ziegen kontextspezifische Variablen einen Einfluss auf die Anpassung der Auslandsmitarbeiter.
Keywords: Auslandsaufenthalt; Kulturelle Anpassung; Persönlichkeit; Personalpolitik; Auslandsmitarbeiter; 150 Psychologie